The waning of the WIMP? A review of models, searches, and constraints - Giorgio Arcadi; Maíra Dutra; Pradipta Ghosh; Manfred Lindner; Yann Mambrini; Mathias Pierre; Stefano Profumo; Farinaldo S. Queiroz (European Physical Journal C: Particles and Fields, 2018)
Abstract Weakly Interacting Massive Particles (WIMPs) are among the best-motivated dark matter candidates. No conclusive signal, despite an extensive search program that combines, often in a complementary way, direct, indirect, and collider probes, has been detected so far. This situation might change in near future due to the advent of one/multi-TON Direct Detection experiments. We thus, find it timely to provide a review of the WIMP paradigm with focus on a few models which can be probed at best by these facilities. Collider and Indirect Detection, nevertheless, will not be neglected when they represent a complementary probe.